On the collections of texts to the history of the Polish language and their titles - Migdał, Jolanta; Walczak, Bogdan (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The article contains a review of collections (anthologies) of texts to the history of the Polish language from the mid-19th century until today. The authors put special emphasis on the anthologies which are most commonly utilized in university didactic, i.e., the anthologies edited by Stefan Vrtel-Wierczyński, Witold Taszycki and the editorial team of Wiesław Wydra and Wojciech Ryszard Rzepka (in this respect it is difficult to form an opinion about the most recent, collective Łódź – Zielona Góra selection of texts edited by Marek Cybulski as it has just appeared in bookshops). On the background of rather schematic titles of anthologies (Selection of texts, Review, Exceptions, Written monuments, Texts etc.) an outstanding work is the Old-Polish Chrestomathy by Wydra and Rzepka. Thus, the authors conclude their paper by explaining the word chrestomathy.